2018
DOI: 10.1016/j.tranon.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Background Parenchymal Enhancement (BPE) in a High-Risk Population: What Causes BPE?

Abstract: OBJECTIVE: To investigate promoting factors for background parenchymal enhancement (BPE) in MR mammography (MRM). METHODS: 146 patients were retrospectively evaluated, including 91 high-risk patients (50 BRCA patients, 41 patients with elevated lifetime risk). 56 screening patients were matched to the high-risk cases on the basis of age. The correlation of BPE with factors such as fibroglandular tissue (FGT), age, menopausal status, breast cancer, high-risk precondition as well as motion were investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…One hypothesis is that mutations in the BRCA gene and its associated sites activate the hormone receptor negative subtype-specific pathway, and the oncogene mediates DNA replication stress, thus directly triggering and promoting tumour progression (22). In this study, the BRCA-positive group, especially the BRCA1 mutation carrier group, had a significantly higher number of triple-negative breast cancers, which is in line with previous literatures (4,6,7,23). The absence of oestrogen receptors and progesterone receptors may lead to a decrease in BPE in BRCA mutation carriers.…”
Section: Discussionsupporting
confidence: 91%
“…One hypothesis is that mutations in the BRCA gene and its associated sites activate the hormone receptor negative subtype-specific pathway, and the oncogene mediates DNA replication stress, thus directly triggering and promoting tumour progression (22). In this study, the BRCA-positive group, especially the BRCA1 mutation carrier group, had a significantly higher number of triple-negative breast cancers, which is in line with previous literatures (4,6,7,23). The absence of oestrogen receptors and progesterone receptors may lead to a decrease in BPE in BRCA mutation carriers.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, there was only moderate correlation between quantitative and visual evaluation. This is certainly explained by the significant inter-observer variability of the 4-grade visual assessment, the presence of motion-induced artifacts (as the visual evaluation was done on subtracted uncorrected series) 28 as well as the difficulty to visually assess BPE in mainly fatty breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Background parenchymal enhancement is a normal breast tissue enhancement on MRI [ 21 ]. Leddy has reported that moderate and marked BPE, which is difficult to differentiate from non-mass enhancement, is a cause of incorrect determinations and it is a diagnostic limitation of MRI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%